Role of Civil Society in Improving Governance. - Raghav Dhawan & Shuchita Bhushan (NLUJ, 2009)
The role of effective governance is vital with regards to non-profit organizations (NPO) considering their continuous rise in size and importance of late. The Board's role in the management of the organization is evolving and their contribution is pertinent for meeting their goals successfully. Since most of the funding provided to the NPOs come from external sources, transparency and accountability are of prime relevance. The governance mechanism is brought into force to ensure that the work done, especially at the grass root level, is duly evaluated and can stand public scrutiny. This will allow the authenticity of their work to be adjudged thereby guaranteeing continued funding by the public The principles of corporate governance have been implemented in the for-profit sector in the recent past. However, the specific character of the non profit sector, i.e. goal structure, specific configuration of ownership rights, multi-stakeholder character, resource mix, culture, makes it difficult to implement these principles directly. They have to be adapted to fit the unique structure of NPOs. Though researchers have been grappling with this issue a formalized framework is yet to be developed. The most frequent application of the principles of governance with respect to the NPOs is the establishment of the Board but other mechanisms are also being developed. The article will address the issues of the lack of a formal model of governance for the non profit sector and also discuss the importance of effective governance of NPOs especially in the Indian context. Such a model is of key importance in India due to the large number of NPOs operating at grass root levels with the nation's underprivileged population. These need a more effective governance to be able to perform their functions more effectively and yet maintain a high degree of accountability.
Keywords: Non-profit organizations (NPOs); Corporate governance; Board accountability; Transparency and disclosure; Governance framework for NPOs; Public trust and funding; Multi-stakeholder management; Non-profit sector in India; Grassroot organizations; Adaptation of governance principles